PENGARUH PERSEPSI, TINGKAT PENDAPATAN, DAN PROMOSI BANK TERHADAP KEPUTUSAN INVESTASI PRODUK REKSADANA (Studi Pada Nasabah Perbankan Selaku Investor Reksadana Kota Cirebon) - Micki Watulandi (Universitas Kuningan, 2022)
This research is aimed to find out influence of perception, income level, and promotion in invesment decisions through a mutualfund product. The methode of collection sample used purposive sampling with criteria: respondence must be bank customer as an investor mutualfund product in Cirebon city. The number of samples are 100 respondences. The methode used in this research is quantitive approach descriptive with model linier double regretion with SPSS 16 version. The result show that instrument in quetionnaier to be stated valid and reliable. The coefficient of determination (R square) in this research is equal to 59,3% of perception, income level,and promotion influence invesment decision through a mutualfund product, while 40,7% is explained by other factors. Simultaneously result show the variables of perception, income level, promotion influence invesment decision through a mutualfund product this is indicated by the value of F (16,044) F table (3,28). Partially in this research result show the variables of perception and promotion are siginificantly influence of invesment decision through a mutualfund product, and the variable of income level is significantly influence invesment decision through a mutualfund product.